Rekam Jejak Keseruan Festival Generasi Pemenang Season 2 - Dewi Sekar Laras Jati; Mahimma Romadhona (Student Research Journal, 2023)
Festival Generasi Juara Season 2 is an event that attracts attention as a forum for developing young generation talents and also Islamic da'wah. This study aims to record and analyze the excitement and impact generated by this festival, especially in the context of developing the next generation in Islamic knowledge.The results highlight that this festival has become an inspiring platform for the younger generation to express their creativity in the field of Islamic art skills such as banjari and Musabaqah Hifdzil Qur'an (MTQ). In addition, the positive impact of this event can be seen in increasing self-confidence while celebrating the Prophet's Mawlid.